2022
DOI: 10.3389/fpls.2022.900143
|View full text |Cite
|
Sign up to set email alerts
|

Combining Proteomics and Metabolomics to Analyze the Effects of Spaceflight on Rice Progeny

Abstract: Spaceflight is a special abiotic stress, the biological effect mechanism of which on contemporary rice has been clarified, However, its effect on offspring rice was still unclear. In order to understand the response mechanism of F2 generation plants to space flight, this study used SJ-10 recoverable satellite to carry DN423 rice seeds for 12.5 days in orbit flight. After returning to the ground, the plants were then planted to F2 generation to explore the biological effect mechanism. Our research showed that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Multiple studies conducted in ISS revealed significant changes in hormonal, amino acid, protein biosynthesis, and redox homeostasis in plants due to short-term spaceflight [5,[22][23][24][25]. The latter phenomena suggest that the response variations to spaceflight seed storage are highly species and varietal dependent, and there are great prospects for quick space plant breeding to produce crops with shortened vegetation phases, high yields, and resistance to diseases [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies conducted in ISS revealed significant changes in hormonal, amino acid, protein biosynthesis, and redox homeostasis in plants due to short-term spaceflight [5,[22][23][24][25]. The latter phenomena suggest that the response variations to spaceflight seed storage are highly species and varietal dependent, and there are great prospects for quick space plant breeding to produce crops with shortened vegetation phases, high yields, and resistance to diseases [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of spaceflight on seed vigor and genetic changes has been the object of many investigations aiming to increase the rate of breeding [1][2][3][4][5][6][7][8]. The exposure of seeds to radiation and microgravity during storage at the ISS greatly affects gene expression [9], causing mutations [10], chromosome aberration [11] and morphological changes [12].…”
Section: Introductionmentioning
confidence: 99%
“…The ion beam technique can induce broad-spectrum mutations at high frequencies, resulting in pronounced biological effects while minimizing damage to target species and ensuring stable inheritance of mutations, making it an ideal method for breeding new cultivars [2,3]. So far, this method has already been widely applied to conduct mutagenesis studies of various plants, including maize, rice, wheat, and Arabidopsis [4][5][6]. However, few studies have used ion beam irradiation technology to breed new hot pepper cultivars.…”
Section: Introductionmentioning
confidence: 99%